Bone mineral density differences between swimmers and soccer players in different age groups - Colantonio, E.; Juzwiak, C. R.; Scorine, C.; Madureira, F.; Clemente, J.; Pinheiro, M. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
During childhood and adolescence, bone mineral density (BMD) increases until the peak bone mass is reached in adulthood. Physical activity has been proposed as a major determinant of BMD. The osteogenic effect of exercise can be attributed mainly to the impact and mechanical loads applied to the bone; however, not all physical activities have the same effects on bone. Duration and intensity are factors which will affect the osteogenic stimulus produced [1, 2, 3]. Recent literature reviews have shown that high impact sports seem to be more osteogenic than non impact sports such as swimming or cycling, in children [4], young adults [4, 5] or older adults [6]. Some studies showed that athletes from other sports presented BMD values much higher than swimmers [7, 8]. A lot of investigations have been produced approaching this theme; nevertheless, results among studies remain disparate [7-12]. Therefore, further investigations in this area are needed in order to elucidate the effect of swimming on BMD.